Kelekatan Ayah-Anak sebagai Media Dasar Memberfungsikan Kejiwaan Positif Anak - Azam Syukur Rahmatullah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2018)
Abstract: The Father having a great responsibility to care for the children, and they can not avoid it.The Result of the research is show if the father have to develop nearly and care attachment to the children since early (unborn child). Several done by the father; give attention to a baby, the dialogue with a baby, reading a prayer to a baby, touching a baby while wife’s pregnancy. In the other hand, a father have to become “like a mother” after the baby born; wear and change the diapers, follow a mom to cleaning the faces, giving a milk, carry on a baby, and hug a baby. On going process to be an adult, a father must increasing to improve the attachment to the children, although he is busy. Communication between father to children or children to father should built by warm and intimate condition, and have to continuing. Hopely, The warm and intimate communication can make positive soul and alive soul to the children.